Ape escapes! : and more true stories of animals behaving badly - Newman, Aline Alexander (Washington, D.C. : National Geographic Society, 2012)
Looks at an ape, puppy, and a cat behaving badly.
Includes bibliographical references (p. 111) and index.
3.8
K-3
Keywords: Animal behavior -- Juvenile literature; Animal behavior; Animal behavior